Role of Culture in Foreign Language Teaching (Siddhajyoti Interdisciplinary Journal, 2025)
This paper deals with the role of culture in foreign language teaching. Teaching and learning foreign language does not mean only acquiring linguistic competence but also acquiring cultural competence. The aim of this paper is to explore the role of culture for effective foreign language teaching. Since this paper is based on the analysis of secondary data, it is claimed to be a reference material for those who want to know the significance of culture in foreign language teaching.  It has been prepared by doing meta-analysis of secondary data obtained from library research through the Internet. It reveals that cultural knowledge is a key prerequisite for meaningful foreign language teaching. Culture plays a crucial role to make learners understand and communicate a foreign language more accurately and appropriately in real life situation. Learning a new language without familiarity with its cultural aspects remains incomplete. To achieve successful foreign language teaching, greater emphasis should be placed on the cultural aspects of language by curriculum designers, textbook writers, and teachers. It is significant to think about the crucial role of culture in foreign language teaching to make students communicate and collaborate cross-culturally in the present context.